2015
DOI: 10.1111/inr.12190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of individual reminiscence therapy for older women living alone

Abstract: Individual reminiscence therapy can be utilized as a nursing intervention for improving memory, cognition and quality of life of older women in the nursing practice. Health policy needs to give attention to health issues of older women living alone. Individual reminiscence therapy can be utilized as a nursing intervention for improving memory, cognition and the quality of life of older women. Health policy needs to give attention to health issues of older women living alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
8
0
1
Order By: Relevance
“…Some studies have reported the effect of reminiscence on quality of life of residents in long‐term care facilities (O'Shea et al . ), or in older women living alone (Sok ). Reminiscence therapy can be used to protect mental health and to improve quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have reported the effect of reminiscence on quality of life of residents in long‐term care facilities (O'Shea et al . ), or in older women living alone (Sok ). Reminiscence therapy can be used to protect mental health and to improve quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that reminiscence interventions affect a wide range of outcomes (nine result variables were defined) in the field of cognitive performance, ego integrity, depression, social integration, positive wellbeing, a sense of meaningfulness to life, etc. Some studies have reported the effect of reminiscence on quality of life of residents in long-term care facilities (O'Shea et al 2014), or in older women living alone (Sok 2015). Reminiscence therapy can be used to protect mental health and to improve quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, our training showed in HE and MCI subjects positive medium effects on memory after training that were also maintained at follow‐up. Although two recent studies in HE evidenced significant positive effects after RT on global cognition and memory (Akhoondzadeh et al ., ; Sok, ), in our study, the addition of RT does not seem to increase the effectiveness. Indeed, the effects in HE and MCI participants on memory are similar to those reported in previous pb‐CT trials.…”
Section: Discussionmentioning
confidence: 99%
“…Various lifestyle factors, including smoking, drinking alcohol, drinking coffee, and exercising, are also considered as influencing factors, apart from genetic factors and nutrition factors, including vitamin B6, B12, and folic acid deficiency (Nygard al., 1995). Cognitive function was found to be improved using various cognitive-based intervention programs (e.g., imagery using video tapes, food list learning, image-name connection method, massed practice, paired-associate learning, relaxation technique, and reminiscence therapy) in studies of older adults or MCI patients (Bohlmeijer, Roemer, Cuijpers, & Smit, 2007;Sok, 2015;Subramaniam & Woods, 2012;Webster & Gould, 2007;Zhou et al, 2012).…”
Section: Introductionmentioning
confidence: 99%